TVET programme and health-related quality of life among low-income populations during the COVID-19 pandemic in Malaysia - Yasin, Ruhizan Mohammad; Tan, Maw Pin; Said, Mas Ayu; Rasul, Mohd Sattar; Thangiah, Nithiah; Rizal, Hussein; Magli, Amirah Shazana; Ithnin, Muslimah; Majid, Hazreen Abdul; Ismail, Rozmi; Su, Tin Tin (Frontiers in Public Health, 2024)
Education improves the economy and quality of life. The availability of skilled education in Malaysia is not restricted to the younger generation but is available to people of all ages, including those with low incomes. This study used the EuroQol 5-Dimension 5-Level (EQ-5D-5L) tool during the COVID-19 pandemic to examine relationships between socio-demographics, knowledge, and attitudes toward education and outcomes of health-related quality of life (HRQOL). Between September and October 2020 and January and February 2021, a cross-sectional study using a multi-stage sampling technique was carried out. A total of 1,997 adults participated, with a mean age of 45.17 (SD 14.113). 74.9% had good knowledge, while 59.8% had a positive attitude towards skill education. In univariate analyses, the EQ-5D-5L score was related to age, income, education level, marital status, employment status, financial strain level, and knowledge and attitude toward skilled education. Generalised linear model analyses demonstrated that lower EQ-5D-5L scores were associated with older age, financial constraints, and a negative attitude toward skills education. However, additional adjustments for knowledge and attitude toward skills education shows only an increase in age and financial strain was significant. The findings suggest that appropriate strategies be implemented to increase low-income populations’ knowledge and attitude toward skill education. Improving education may improve the quality of life for this vulnerable group. Additionally, a qualitative study can be conducted to determine the barriers to low-income households participating in skilled education to fill in the knowledge gap.